Annotated bibliography of Quaternary vertebrates of northern North America : with radiocarbon dates - Harington, C. R., 1933- (Published by the University of Toronto Press in collaboration with the Canadian Museum of Nature, 2003)
"This book is the first annotated bibliography of Quaternary vertebrates of Canada, Alaska, and Greenland. It focuses on highlights (species mentioned, locality, geological age, stratigraphic positions, etc.) of more than 1300 items published for the most part between 1821 and 2000, dealing with the remains of fishes, amphibians, reptiles, and, mainly, mammals that lived from about two million to five thousand years ago. A significant feature of the book is the extensive radiocarbon-date table - a first attempt to systematically and comprehensively record direct dates on vertebrate fossils from northern North America. Featuring more than 2000 dates listed by genus, species, date, laboratory number, locality, specimen, description, and references/remarks, this table will allow students of extinctions - particularly near the end of the Pleistocene about ten thousand years ago - a much clearer view of their nature and timing in northern North America."--Jacket